Are there any negative career consequences for executives and directors working in stigmatized industries? - Osiichuk, Dmytro (Publishing House of Wroclaw University of Economics and Business, 2022)
This study found no evidence of the adverse effects for executives and board members employed by firms operating in ‘stigmatized’ industries such as tobacco, alcohol, and gambling. The records disclosed by public companies from 21 EU countries suggest that executive and director remuneration in ‘sin’ industries is not significantly different from that in other industries. The composition of the supervisory boards in terms of directors’ independence, industry-specific skills and average tenure is not dissimilar from other industries, suggesting the lack of negative consequences for career and networking opportunities related to working for firms with a perceived negative public image. Board members enjoy a similar number of external affiliations and outside directorships. Tobacco industry companies are found to be more likely to offer golden parachutes to their executives, enforce limitations on director removal and mandatory limits to board memberships. No other industry-specific corporate governance settings were documented. From the financial standpoint, working for firms in stigmatized industries is not associated with increased reputational risks, as neither accounting controversies nor earnings restatements are more probable in these firms than in other industries.
Argumenta Oeconomica, 2022, Nr 1 (48), s. 101-130
Keywords: executive compensation; corporate governance; social stigma